The Ideal Man "The Prophet Mohammed" (Pba) Reflected In Nahjul Balaghah Analytic Study - Ahmad, Adnan; Omran, Montajab (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The research looks at the image of the ideal man represented by the character of prophet Mohammed (pba) that is dealt with by Imam Ali in 'NahjulBalaghah' . The research begins by showing the opinion of some philosophers in man in general and the ideal man in particular . then , it moves to deal with 'the ideal man' . the idea that occupies most of the research .it studies that in accordance with a preface which refines the characteristics of Prophet Mohammed supervened by one of Imam Ali`s speeches in which he mentions the characteristics of the prophet (pba)to make it abvious the characteristics of the ideal man or what the expected image of man should be that's all done in a mere, distinct , technical , linguistic from . the research sheds alight on man's different deeds and his multi – aspect elements prevailing the appealing aspects in the speech and the impact of technical images , the language , the cadence in exposing the image of the ideal man- the prophet himself making its context and the speech it put within very clear .